Pengawasan Pengurus Ikatan Notaris Indonesia Kota Padang Terhadap Pelaku Pelanggaran Kode Etik - Nisaul Hasanah; Azmi Fendri; Neneng Oktarina (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract.Notary is a profession that demands office holders and the profession has scientific competence and moral competence. Based on the code of ethics, the results of the changes are interesting to see the supervision and enforcement of a code of ethics for notaries who violate the code of ethics by the board of the Indonesian Notary Association (INI). Supervision and enforcement of a notary code of ethics by the Management of the Indonesian Notary Association in the city of Padang is carried out by the Regional Honorary Council. Supervision and enforcement of the code of ethics is carried out in a multilevel manner, if a suspected violation of the code of ethics is not satisfied with the decision of the regional or regional council of honor, then an appeal can be made against the Central Honorary Council. If it has not been satisfied with the decision of the Central Honorary Board, it can be appealed to Congress. While legal issues that arise related to supervision of a Notary who violates the code of ethics by the Management of the Indonesian Notary Association in the City of Padang, namely the inadequacy of rules related to the notary examination event by the Honorary Board of the Notary Association of Indonesian Notaries.Keywords: Supervision, Violation, Code of EthicsAbstrak. Notaris merupakan sebuah profesi yang menuntut pemangku jabatan dan profesi tersebut memiliki kompetensi keilmuan dan kompetensi moral. Berdasarkan kode etik hasil perubahan terlihat pengawasan dan penegakan kode etik terhadap notaris yang melakukan pelanggaran kode etik oleh pengurus Ikatan Notaris Indonesia (INI). Pengawasan dan penegakan kode etik notaris oleh Pengurus Ikatan Notaris Indonesia kota Padang dilaksanakan oleh Dewan Kehormatan Daerah. Pengawasan dan penegakan kode etik dilaksanakan secara bertingkat. Apabila terduga pelanggaran kode etik tidak puas dengan keputusan dewan kehormatan daerah, maupun wilayah, maka dapat mengajukan banding terhadap Dewan Kehormatan Pusat. Jika belum terpuaskan dengan putusan Dewan Kehormatan Pusat, maka bisa diajukan banding ke Kongres. Permasalahan hukum yang timbul terkait pengawasan terhadap Notaris yang melakukan pelanggaran kode etik oleh Pengurus Ikatan Notaris Indonesia di Kota Padang yaitu belum memadainya aturan-aturan terkait acara pemeriksaan notaris oleh Dewan Kehormatan Notaris Ikatan Notaris Indonesia.Kata Kunci: Pengawasan, Pelanggaran, Kode Etik